2021
DOI: 10.1371/journal.pmed.1003455
|View full text |Cite
|
Sign up to set email alerts
|

The potential shared role of inflammation in insulin resistance and schizophrenia: A bidirectional two-sample mendelian randomization study

Abstract: Background Insulin resistance predisposes to cardiometabolic disorders, which are commonly comorbid with schizophrenia and are key contributors to the significant excess mortality in schizophrenia. Mechanisms for the comorbidity remain unclear, but observational studies have implicated inflammation in both schizophrenia and cardiometabolic disorders separately. We aimed to examine whether there is genetic evidence that insulin resistance and 7 related cardiometabolic traits may be causally associated with schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 59 publications
3
60
0
Order By: Relevance
“…The mechanism of comorbid insulin resistance is still unknown, but observational studies have implicated inflammation in both schizophrenia and insulin resistance [2]. Genome-wide association studies support a role for inflammation as a common cause of schizophrenia and insulin resistance, which could partly explain why the traits commonly co-occur in clinical practice [3]. Probiotics can help regulate the immune system and anti-inflammatory response [4].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of comorbid insulin resistance is still unknown, but observational studies have implicated inflammation in both schizophrenia and insulin resistance [2]. Genome-wide association studies support a role for inflammation as a common cause of schizophrenia and insulin resistance, which could partly explain why the traits commonly co-occur in clinical practice [3]. Probiotics can help regulate the immune system and anti-inflammatory response [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, understanding the determinants of metabolic variability could provide insight into the biological processes underlying psychosis. For example, a shared role for inflammation in insulin resistance and schizophrenia has been proposed (Perry et al, 2021); however, an inflammatory state may only be seen in a subgroup of patients (Pillinger et al, 2019b), which would explain the metabolic heterogeneity findings documented in the current study. Unfortunately, no studies included in the current meta-analysis provided inflammatory mediator data, precluding a meta-regression analysis exploring the moderating effects of such parameters on metabolic effect size magnitudes.…”
Section: Discussionmentioning
confidence: 71%
“…However, in FEP cases Lis et al, (2020) observed a correlation between leptin and cognitive dysfunction, a domain of psychopathology somewhat linked to negative symptoms. Recently, a Mendelian randomisation (MR) study did not find an association between leptin and schizophrenia (Perry et al, 2021a), bringing into question whether leptin plays a causal role in the illness. It is worth noting that this MR analysis relied on GWAS of schizophrenia, and not that of negative symptoms specifically.…”
Section: Discussionmentioning
confidence: 99%